Pemberdayaan Peer Grup dalam meningkatkan Kesehatan Jiwa Remaja di SMP NEGERI 5 Sumbawa Besar - Lina Eta Safitri; Putri Adekayanti; Meliana Fitri; Ovi Soviya (Universitas Kristen Indonesia Toraja, 2025)
Adolescent mental health is an increasingly pressing issue, especially in educational settings. At SMP Negeri 5 Sumbawa Besar, many teenagers face mental health challenges, such as anxiety and depression, which can affect their well-being. This research aims to evaluate the effectiveness of peer group empowerment programs in improving adolescent mental health. Evaluation results showed a significant increase in students' knowledge about mental health after participating in the program, with more than 80% of students feeling more understanding about how to maintain mental health. In addition, this program successfully creates a supportive environment between peers that reduces feelings of loneliness and increases students' self-confidence. Thus, peer group empowerment has proven to be effective in improving the mental health of teenagers at SMP Negeri 5 Sumbawa Besar, as well as making a positive contribution to social dynamics at school. It is hoped that this program can become a model for other schools in efforts to promote adolescent mental health.